Understanding Suicidal Behaviour and Distress in Young Muslim Canadians: A Qualitative Study - Hussain, Zakia; Furqan, Zainab; Saunders, Natasha; Madda, Nabiha; Javeed, Imaan; Kurdyak, Paul; Husain, Ishrat; Sinyor, Mark; Malick, Arfeen; Zaheer, Juveria (International Journal of Medical Students, 2023)
BACKGROUND: Suicide is a major public health concern worldwide, including in Canada. The onset of major mental illnesses occurs during adolescence and young adulthood. Among this group, young Muslims in Canada may be particularly vulnerable due to unique stressors and emerging evidence indicating that Muslims in the U.S. report more suicide attempts than other religious groups. To our knowledge, no prior study has undertaken an in-depth exploration of the lived experiences of Muslim young adults who have attempted suicide. This study aims to broaden our understanding of how Muslim young adults experience and understand suicidal behavior by exploring narratives of distress and help-seeking, the meanings of suicidal behavior, the impact of immigration/resettlement, discrimination, Islamophobia, and the role of negotiating multiple religious, cultural, and gender identities. METHODS: This study is currently in progress. We are recruiting approximately 25-30 Muslim youth between the ages of 15-24 who have experienced suicidal behavior with any intent to die, as reported by the participants themselves, within the Greater Toronto Area (GTA). Exclusion criteria include (1) active substance intoxication or withdrawal, (2) current admission to a psychiatric facility, and (3) low levels of intellectual functioning or a history of neurological impairment. We are conducting heterogeneous purposive sampling to ensure that our sample includes diversity in terms of gender, age, countries of origin, and first and second-generation youth. Recruitment will end when data saturation is reached. Each participant will take part in a semi-structured qualitative interview. The interview explores family and social contacts, immigration/acculturation experiences, gender and cultural roles, and views on religion. Data is being transcribed and analyzed in N-Vivo 12 software using constructivist grounded principles entailing simultaneous collection and analysis, inductive construction of abstract categories explaining social processes, sampling and categorical refinement through iterative analysis, and integration of categories into a theoretical framework. RESULTS: Preliminary data analysis is in progress based on participants (n=15) recruited thus far. Emerging themes in relation to the causes of suicidality include isolation and an inability to cope with multiple stressors, such as family conflict and physical illness. Religion has a varied effect on suicidality, ranging from minimal to strong influence and from being protective to triggering suicidality. Regarding barriers to care, emerging themes included fear of invalidation, Islamophobia, and the lack of cultural safety within the healthcare system. Notably, youth appear to have a different explanatory model for mental illness compared to their family/community. CONCLUSION: This is the first qualitative study examining the experiences of Canadian Muslim youth who have experienced suicidal behavior. Our findings will help elucidate the unique stressors and protective factors that influence suicide and suicidal behavior for Canadian Muslim youth. Understanding patterns of distress and barriers to care through qualitative analysis will provide critical context to ultimately develop appropriate and effective screening, service provision, and suicide prevention strategies.